Magnetic recovery reveals sequential extraction bias and supports mass-conservative assessment of lanthanum-based sediment phosphorus inactivation - Zhe Wang; Liling Wang; Chengyan Bao; Enyang Liu; Xinnuo Liu; Zezhen Pan; Feijian Mao; Xingxing Wang; Jiake Li; Deyi Wu; Qiang Xie; Zimeng Wang (Water Research, 2026)

PdO-T nanozyme-based three-channel colorimetric sensor array coupled with machine learning for accurate differentiation and quantitative detection of aflatoxins in U.S. pecan - Yanbin Wang; Liling Wang (Food Research International, 2026)

Characterization and modification of chickpea husk dietary fibers: Potential applications in gummy candy and emulsion-based food products - Xiangyu Liu; Yifan Zhang; Liang Wang; Minwei Zhang; Fen Li; Huiling Yan; Kaiwen Wu; Feng Zhang; Qiao Zhang; Jun Liu; Chunlan Zhang; Liling Wang; et al. (Food Hydrocolloids, 2026)

Metabolic division of labor drives synergistic production of biomass, lipid and α-tocopherol in Euglena gracilis–Chlorella pyrenoidosa co-cultures - Zhen Wang; Qisheng Tian; Liling Fu; Xiaofan Xing; Wei Liu; Changhong Liu; Lei Zheng (Bioresource Technology, 2026)

Effects of ultrasound, blanching, and ethanol pretreatments on drying characteristics, microstructure, and quality of apricots using hot air-assisted radio frequency energy - Jiahong Yuan; Dongsheng Hu; Qianjie Xiong; Rui Li; Liling Yang; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2026)

Synergistic dual-gradient Schottky-junction bilayer hydrogel for high-performance moisture-electric generation - Liling Qin; Shuxin Zhang; Hanxiao Zhang; Caichuang Huang; Can Wang; Yong Wang; Jiulong Sha (Chemical Engineering Journal, 2026)

Distinct patterns of intestinal microbiota and immune responses under acute and chronic ammonia stress in yellow catfish (Pelteobagrus fulvidraco) - Kun Xiao; Liling Nie; Shasha Zhao; Gehan Gao; Cuancheng Zhao; Yanjun Du; Rongfei Hu; Ruru Lin; Jie Wang; Man Wang; Dong Han; Lei Zhang (Aquaculture, 2026)

Aerobic and anaerobic degradation of BDE-47 by facultative anaerobe Pseudomonas sp. QS-1: Pathway, product toxicity, and bio-augmentation remediation - Xin Qi; Ziwei Wang; Qixin Xia; Xiuping Liang; Guiyin Wang; Changlian Xu; Guochun Lv; Junzhuo Cai; Zhang Cheng; Zhanbiao Yang; Liling Wang; Xiaoxun Xu; et al. (Process Safety and Environmental Protection, 2026)

Correction to: Long-Term Monochromatic Light Exposure Does Not Alter Modular Chromatic Representation in the Visual Cortex of Rhesus Monkeys - Wenqing Zhu; Ye Liu; Xiaoxiao Chen; Liling Qian; Wei Wang; Leilei Zou; Yiliang Lu; Rui Liu (Neuroscience Bulletin, 2026)

Concurrent biodegradation of tylosin and tilmicosin by a novel Paracoccus versutus 4-B-2 - Zhengyan Chen; Anqi Liu; Junzhe Cui; Chunhui Liu; Huijuan Li; Ziyi Quan; Yaxu Liu; Xiao Guo; Xiaoyu Wang; Liling Fan; Bo Wang (Journal of Hazardous Materials, 2026)

Heterogeneous catalysis triggered in the novel copper-palladium spinel oxides through electron delocalization and oxygen vacancies for efficient degradation of organic contaminants - Yanbin Wang; Liling Wang (Journal of Environmental Management, 2026)

Long-Term Monochromatic Light Exposure Does Not Alter Modular Chromatic Representation in the Visual Cortex of Rhesus Monkeys - Wenqing Zhu; Ye Liu; Xiaoxiao Chen; Liling Qian; Wei Wang; Leilei Zou; Yiliang Lu; Rui Liu (Neuroscience Bulletin, 2026)

Unraveling the Low Residual Mechanism of Polycyclic Aromatic Hydrocarbons in Rice Grains Driven by Low Moisture Regulation: Microbial Mediated Health Effects - Zhenhua Zhao; Xiaorou Wang; Yueli Liu; liling Xia; Zhirui Qin; Jingjing Cao; Harry Toland (Journal of Soil Science and Plant Nutrition, 2026)

Increasingly frequent compound climate events worsen economic disparities in China's urban agglomerations - Chao He; Liling Chu; Yiqi Zhou; Yanwen Wang; Yilin Li; Qixin Hu; Song Hong; Chunping Miao (Urban Climate, 2026)

TMC6 Protects Against Ischemic Neuronal Injury by Activating Rap1/Rac1 Signaling to Restore Mitochondrial Dynamics and Mitophagy - Xuemei Quan; Huo Liang; Haiyin Long; Xiawei Wang; Liling Feng; Xia Zhou; Yuan Chen; Yanhua Li; Xiaofeng Li (Molecular Neurobiology, 2026)

Study on PFAS removal by different forms of iron-modified biochar: Adsorption effects and catalytic activity - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuanchi Wang; Jiayuan Cheng; Wenqing Zhang; Hailong Wang (Journal of Environmental Chemical Engineering, 2025)

Study on the effect of alginate coated Ca-Fe bimetallic composite biochar microspheres on the removal of short-chain PFAS - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuanchi Wang; Hailong Wang; Olive M. Yemele; Muhammad Adnan (Environmental Research, 2025)

Assessment of potentially toxic elements (PTEs) in surface and groundwater of volcanic and granite regions of Hainan Island, China: Pollution status, sources, and health risk evaluation - Jianzhou Yang; Yong Li; Shengyue Liang; Min Zhang; Jingjing Gong; Yufang Li; Qiankun Yan; Xiaohui Sun; Zuyang Xu; Xueju Liu; Shuqi Hu; Jianweng Gao; et al. (Environmental Geochemistry and Health, 2025)

Contact-dependent antagonism is mediated by a T7SSb toxin effector–immunity protein pair via ADP-ribosylation - Hongxin Guan; Huan Wu; Mengrou Gan; Jing Zhang; Jiajun Wang; Siyao Liu; Shuyue Chen; Yindi Jiao; Fan Li; Shiqing Huang; Sihuang Lin; Hongwei Chen; et al. (Science Bulletin, 2025)

Effect of salt valence and ionic strength on the rheology and 3D printing performance of walnut protein emulsion gels - Guohua Li; Bo Wang; Liling Yang; Weiqiao Lv; Hongwei Xiao (Food Hydrocolloids, 2025)

Suitability evaluation of measurement method for radon exhalation rate of porous medium containing radon adsorbing materials - Haofeng Wang; Yongjun Ye; Xuanli Yao; Liling Luo (Journal of Hazardous Materials, 2025)

Unraveling microbial assembly and co-occurrence relationship at seasonal and vertical scales in an aged organic-contaminated site - Zhirui Qin; Zhenhua Zhao; Liling Xia; Jiayuan Liu; Xuan Li; Aiwei Zhang; Yue Wang; Jingwei Wang (International Biodeterioration & Biodegradation, 2025)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

A global systematic review and meta-analysis of innovative technologies for 1,2,4-trichlorobenzene remediation in soil and water - Olive Mekontchou Yemele; Zhenhua Zhao; Mbezele Junior Yannick Ngaba; Ervice Ymele; Liling Xia; Wang Xiaorou; Prince Atta Opoku (Environmental Geochemistry and Health, 2025)

Fluorescent nanozyme for the dual-mode detection of tetracycline: Aggregation-induced luminescence and boosting peroxidase-like activity - Tai Ye; Long Bai; Jinsong Yu; Weiyan Shi; Min Yuan; Juncheng Wang; Hui Cao; Liling Hao; Xiuxiu Wu; Fengqin Yin; Fei Xu (Food Control, 2025)

A multiplex RT‑PCR detection system for pepper co-infection by three potyviruses - Tiyuan Xia; Liling Mo; Xinyang Chen; Wang Wang; Pengyu Liu; Xingmei Tao; Xuan Yi; Zuqin Qiao; Yongfu Zhang; Xiaoqin Li (Journal of General Plant Pathology, 2025)

Legumes reduce the effects of salt stress on co-existing grass - Liling Liu; Ziyan Chen; Xiaomei Gou; Lingcao Hou; Chenglong Liang; Huan Jiao; Weibo Kong; Liping Qiu; Xiang Wang; Xiaorong Wei (Journal of Environmental Management, 2025)

Clinical Diagnosis and Differential Diagnosis Between CSF1R- and AARS2-Related Leukoencephalopathy - Chenhui Mao; Yuyue Qiu; Tianyi Wang; Yuhan Jiang; Shanshan Chu; Wei Jin; Liling Dong; Jing Gao (Journal of Molecular Neuroscience, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

Revealing the active ingredients and mechanisms of Xiatianwu against hepatocellular carcinoma: a study based on network pharmacology and bioinformatics - Hui Wang; Weina Zhang; Liling Li; Hong Wang; Honglin Jiang; Wenna Li; Jinchang Huang; Yuxiang Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Progress on the removal of PFAS contamination in water by different forms of iron-modified biochar - Binglu Teng; Zhenhua Zhao; Liling Xia; Jiangxuan Wu; Hailong Wang (Chemosphere, 2024)

Comparative lipidomics analysis of seed oils from nine tropical fruits: Emphasizing the fatty acid and lipid molecule profiles - Jingtao Cui; Tong Li; Yanchi Zhou; Liling Wang; Tian Li; Weimin Zhang (Food Research International, 2024)

Lactococcus lactis subsp. lactis LJL7m20 strongly inhibits growth of the Bacillus cereus group from sufu - Jialu Xian; Huifang Wang; Siying Diao; Nan Zhang; Sisi Lin; Rui Zhang; Zekun Jin; Zhaohui Zhou; Liling Lu; Sameh A. Korma; Li Li (Food Bioscience, 2024)

Bimetallic MOF-derived three-dimensional nanoflowers PdCoOx as peroxidase mimic activity for determining total antioxidant capacity - Liling Wang; Yanbin Wang; Yifeng Zhou (Food Chemistry, 2024)

Effect of κ-carrageenan on physicochemical and 3D printing properties of walnut protein-stabilized emulsion gel - Guohua Li; Bo Wang; Weiqiao Lv; Liling Yang; Hongwei Xiao (Food Hydrocolloids, 2024)

Insight into selenium biofortification and the selenite metabolic mechanism of Monascus ruber M7 - Lisha Zhu; Pengcheng Long; Man Hu; Liling Wang; Yanchun Shao; Shuiyuan Cheng; Xingxing Dong; Yi He (Food Chemistry, 2024)

Glutamicibacter nicotianae AT6: A new strain for the efficient biodegradation of tilmicosin - Huijuan Li; Hao Zhou; Liling Fan; Long Meng; Yanyun Zhao; Lanmei Zhao; Bo Wang (Journal of Environmental Sciences, 2024)

First report of pod pepper vein yellows virus infecting Solanum nigrum L. in China - Yongfu Zhang; Pengyu Liu; Liling Mo; Xinyang Chen; Wang Wang; Xingmei Tao; Xiaoqin Li (Journal of Plant Pathology, 2024)

NLRC3 attenuates osteoclastogenesis by limiting TNFα+ Th17 cell response in osteoporosis - Lingyan Ren; Guangjun Liu; Yun Bai; Liling Gu; Yuan Wang; Li Sun (Journal of Molecular Medicine, 2024)
NOD-like receptor family CARD domain containing 3 (NLRC3) is the intracellular protein belonging to NLR (NOD-like receptor) family. NLRC3 can negatively regulate inflammatory signal transduction pathways within the adaptive and innate immunocytes. However, studies need to elucidate the biological role of NLRC3 in bone remodeling. Herein, our study proved that NLRC3 prevents bone loss by inhibiting TNFα + Th17 cell responses. In osteoporosis, NLRC3 attenuated TNFα + Th17 cell accumulation in the bone marrow. However, osteoporosis (OP) development was aggravated without affecting bone marrow macrophage (BMM) osteoclastogenesis in NLRC3-deficient ovariectomized (OVX) mice. In this study, we transferred the wild-type and NLRC3 −/− CD4 + cells into Rag1 −/− mice. Consequently, we evidenced the effects of NLRC3 in CD4 + T cells on inhibiting the accumulation of TNFα + Th17 cells, thus restricting bone loss in the OVX mice. Simultaneously, NLRC3 −/− CD4 + T cells promoted the recruitment of osteoclast precursors and inflammatory monocytes into the OVX mouse bone marrow. Mechanism-wise, NLRC3 reduced the secretion of TNFα + Th17 cells of RANKL, MIP1α, and MCP1, depending on the T cells. In addition, NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. Collectively, this study appreciated the effect of NLRC3 on modulating bone mass via adaptive immunity depending on CD4 + cells. According to findings of this study, NLRC3 may be the candidate anti-OP therapeutic target. Key messages NLRC3 negatively regulated the Th17 osteoclastogenesis promoting functions via limiting the NF-κB activation. NLRC3 may be the candidate anti-OP therapeutic target.

Multi-omics analysis provides insight into liver metabolism in yellow catfish (Pelteobagrus fulvidraco) under hypoxic stress - Man Wang; Shasha Zhao; Jie Wang; Liling Nie; Li Li; Xiaoming Zhu; Lei Zhang (Aquaculture, 2024)

Effects of intracellular Ca2+ on developmental potential and ultrastructure of cryopreserved-warmed oocyte in mouse - Junping Cheng; Xiaoli Wang; Chan Luo; Xianbao Mao; Jie Qin; Yan Chi; Bing He; Yanrong Hao; Xiangli Niu; Ben Huang; Liling Liu (Cryobiology, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Variations in Blood Copper and Possible Mechanisms During Pregnancy - Lihua Guan; Yifei Wang; Liling Lin; Yutong Zou; Ling Qiu (Biological Trace Element Research, 2024)

Synergistic effects of carbon cap-and-trade and renewable portfolio standards on renewable energy diffusion - Xiongping Yue; Chao Wang; Boxue Sun; Huanyu Ren; Yong Tan; Liling Huang; Dan Feng; Xin Li (Journal of Cleaner Production, 2023)

Study on Strength Characteristics of Interlayer Rocks Based on Thermal–Mechanical Coupling - Liewang Qiu; Liling Zhu; Liangfu Xie; Yongjun Qin; Jianhu Wang; Guangming Yu (Geotechnical and Geological Engineering, 2023)

Influence of Particle Gradation and Penetration Velocity on Deformation Behavior of Sandy Soil Based on CPT - Jianbin Cui; Liangfu Xie; Jianhu Wang; Liling Zhu; Yongjun Qin (Geotechnical and Geological Engineering, 2023)

Nanocellulose-enhanced smart film for the accurate monitoring of shrimp freshness via anthocyanin-induced color changes - Liling Li; Wenxiu Wang; Mengdan Zheng; Jianfeng Sun; Zhizhou Chen; Jie Wang; Qianyun Ma (Carbohydrate Polymers, 2023)

The ecological response and distribution characteristics of microorganisms and polycyclic aromatic hydrocarbons in a retired coal gas plant post-thermal remediation site - Zhenhua Zhao; Barry Mody Oury; Liling Xia; Zhirui Qin; Xiangyu Pan; Jichan Qian; Fangzhou Luo; Yong Wu; Luqi Liu; Wei Wang (Science of The Total Environment, 2023)

A review on chemical and physical modifications of phytosterols and their influence on bioavailability and safety - Simin Feng; Liling Wang; Ping Shao; Peilong Sun; Chung S. Yang (Critical Reviews in Food Science and Nutrition, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

A genome-wide association study reveals that the cytochrome b5 involved in seed reserve mobilization during seed germination in rice - Zhibo Huang; Jifeng Ying; Liling Peng; Shan Sun; Chengwei Huang; Can Li; Zhoufei Wang; Yongqi He (Theoretical and Applied Genetics, 2021)

CircRNA expression profiling and bioinformatics analysis indicate the potential biological role and clinical significance of circRNA in influenza A virus-induced lung injury - Jiajia Wang; Yanbing Zhang; Fengfeng Zhu; Liling Chen; Yao Wei; Qingqing Zhu; Junhong Jiang; Jian-an Huang; Qiang Guo; Xinjing Yang (Journal of Biosciences, 2021)

Temperature changes between neighboring days and childhood asthma: a seasonal analysis in Shanghai, China - Xiaoning Lei; Lijuan Liu; Renjie Chen; Cong Liu; Jianguo Hong; Lanfang Cao; Yanming Lu; Xiaoyan Dong; Xinchang Chen; Xiangwei Qiu; Min Xia; Bo Ding; et al. (International Journal of Biometeorology, 2021)

A Decision-Making Method for Autonomous Collision Avoidance for the Stand-On Vessel Based on Motion Process and COLREGs - Bing Wang; Yixiong He; Weixuan Hu; Junmin Mou; Liling Li; Ke Zhang; Liwen Huang (Journal of Marine Science and Engineering, 2021)
A great number of collision accidents can be attributed to incongruous collision-avoidance actions between the give-way vessel and the stand-on vessel in a crossing or overtaking situation. If the give-way vessel does not take appropriate collision-avoidance action according to international regulations for preventing collisions at sea, the last barrier to pass safely is the appropriate and effective collision-avoidance action taken by the stand-on vessel. To find the proper autonomous collision-avoidance action of the stand-on vessel, a method is proposed that combines quantitative analysis rules of collision-avoidance with the deduction of nonlinear maneuvering motion process based on the mathematical model group, which conformity can reach 90%. This research presents a method to calculate the timing and most effective collision-avoidance actions for the stand-on vessel based on the four-stage theory of encountering vessels and the characteristics of vessel motion. The accuracy of the latest-action timing and the action amplitude for the stand-on vessel can be increased to the level of second and degree, respectively. A novel model of collision risk index is constructed by the latest time of the feasible collision-avoidance action on the precise of different course-altering amplitude. Methods to find the stand-on vessel’s proper collision-avoidance actions in the open sea are presented. The simulation indicates the proposed method for the stand-on vessel can make correct collision-avoidance decisions autonomously.

Phenotype Heterogeneity and Genotype Correlation of MAPT Mutations in a Chinese PUMCH Cohort - Chenhui Mao; Liling Dong; Jie Li; Xinying Huang; Dan Lei; Jie Wang; Shanshan Chu; Caiyan Liu; Bin Peng; Liying Cui; Jing Gao (Journal of Molecular Neuroscience, 2021)

Influence and interaction of iron and lead on seed germination in upland rice - Liling Wang; Bentong Liu; Yanbin Wang; Yuchuan Qin; Yifeng Zhou; Hua Qian (Plant and Soil, 2020)

Carbonyl sulfide (COS) and carbon disulfide (CS2) exchange fluxes between cotton fields and the atmosphere in the arid area in Xinjiang, China - Weiwen Jing; Liling Wang; Deqiang Li; Xiaowei Bao; Yingshuang Shi (Environmental Geochemistry and Health, 2019)

Epidemiological and genetic characteristics of the fifth avian influenza A(H7N9) wave in Suzhou, China, from October 2016 to April 2017 - Zefeng Dong; Yu Xia; Xuerong Ya; Liling Chen; Cheng Liu; Ruyan Wang; Qiang Shen (Virus Genes, 2018)

A new 4-Amino-7-Nitro-2,1,3-Benzoxadiazole (ANBD)-Based Fluorescent Probe for the Detection of Hg2+ - Ke Wang; Xue Mao; Liling Cao; Guoping Lv; Xinfeng Dong; Yan He; Yongju Wei (Journal of Fluorescence, 2017)

Function of quorum sensing and cell signaling in the formation of aerobic granular sludge - Shuo Wang; Wenxin Shi; Tang Tang; Yuying Wang; Liling Zhi; Jinze Lv; Ji Li (Reviews in Environmental Science and Bio/Technology, 2017)

Arsenic Trioxide and Icariin Show Synergistic Anti-leukemic Activity - Zhi Wang; Hong Zhang; Liling Dai; Tongguo Song; Ping Li; Yali Liu; Luning Wang (Cell Biochemistry and Biophysics, 2015)

Identification of fungal genes involved in the preinfection events between ectomycorrhizal association (Pisolithus tinctorius and Pinus massoniana) - Haibo Li; Huazheng Peng; Liling Wang; Hailong Wei; Nan Li; Qunying Jing (Mycological Progress, 2014)

Boletus roseoflavus, a new species of Boletus in section Appendiculati from China - Haibo Li; Hailong Wei; Huazheng Peng; Hongmei Ding; Liling Wang; Liang He; Lizhong Fu (Mycological Progress, 2014)

Optimization of extractants, purifying packings, and eluents for analytical extraction of organochlorine pesticides in Hydragric Acrisols - Zhenhua Zhao; Liling Xia; Fang Wang; Xin Jiang; Yanzheng Gao (Environmental Monitoring and Assessment, 2012)

Nitric oxide enhances salt tolerance in maize seedlings through increasing activities of proton-pump and Na+/H+ antiport in the tonoplast - Yanyan Zhang; Liling Wang; Youliang Liu; Qun Zhang; Qiuping Wei; Wenhua Zhang (Planta, 2006)

Characterization of An Avian Influenza Virus of Subtype H7N2 Isolated from Chickens in Northern China - Yanbing Li; Chengjun Li; Liling Liu; Hongwei Wang; Chuanbin Wang; Guobing Tian; Robert G. Webster; Kangzhen Yu; Hualan Chen (Virus Genes, 2006)